A measurement technique to determine the calibration accuracy of an electromagnetic tracking system to radiation isocenter. Issue 8 (22nd July 2013) - Litzenberg, Dale W.; Gallagher, Ian; Masi, Kathryn J.; Lee, Choonik; Prisciandaro, Joann I.; Hamstra, Daniel A.; Ritter, Timothy; Lam, Kwok L.
Abstract : Purpose: : To present and characterize a measurement technique to quantify the calibration accuracy of an electromagnetic tracking system to radiation isocenter. Methods: : This technique was developed as a quality assurance method for electromagnetic tracking systems used in a multi‐institutional clinical hypofractionated prostate study. In this technique, the electromagnetic tracking system is calibrated to isocenter with the manufacturers recommended technique, using laser‐based alignment. A test patient is created with a transponder at isocenter whose position is measured electromagnetically. Four portal images of the transponder are taken with collimator rotations of 45° 135°, 225°, and 315°, at each of four gantry angles (0°, 90°, 180°, 270°) using a 3 × 6 cm 2 radiation field. In each image, the center of the copper‐wrapped iron core of the transponder is determined. All measurements are made relative to this transponder position to remove gantry and imager sag effects. For each of the 16 images, the 50% collimation edges are identified and used to find a ray representing the rotational axis of each collimation edge. The 16 collimator rotation rays from four gantry angles pass through and bound the radiation isocenter volume. The center of the bounded region, relative to the transponder, is calculated and then transformed to tracking system coordinates using the transponder position, allowing the tracking system's calibration offset from radiation isocenter to be found. All image analysis and calculations are automated with inhouse software for user‐independent accuracy. Three different tracking systems at two different sites were evaluated for this study. Results: : The magnitude of the calibration offset was always less than the manufacturer's stated accuracy of 0.2 cm using their standard clinical calibration procedure, and ranged from 0.014 to 0.175 cm. On three systems in clinical use, the magnitude of the offset was found to be 0.053 ± 0.036, 0.121 ± 0.023, and 0.093 ± 0.013 cm. Conclusions: : The method presented here provides an independent technique to verify the calibration of an electromagnetic tracking system to radiation isocenter. The calibration accuracy of the system was better than the 0.2 cm accuracy stated by the manufacturer. However, it should not be assumed to be zero, especially for stereotactic radiation therapy treatments where planning target volume margins are very small.